Transcriptome Analysis of Immune Response of mIgM+ B Lymphocytes in Japanese Flounder (Paralichthys olivaceus) to Lactococcus lactis in vitro Revealed That IFN I-3 Could Enhance Their Phagocytosis - Tang, Xiaoqian; Yang, Shun; Sheng, Xiuzhen; Xing, Jing; Zhan, Wenbin (Frontiers in Immunology, 2019)
B cells have recently been proven to have phagocytic activities, but few studies have explored the relevant regulation mechanisms. In this study, we showed that 25% of the Japanese flounder (Paralichthys olivaceus) membrane-bound (m)IgM+ B lymphocyte population phagocytosed inactivated Lactococcus lactis with a mean phagocytosis. High-purity mIgM+ B lymphocytes were subsequently sorted to investigate the cellular response to L. lactis stimulation in vitro. Transcriptome analysis identified 1375 differentially expressed genes (DEGs) after L. lactis stimulation, including 975 upregulated and 400 downregulated genes. Many of these DEGs were enriched in multiple pathways associated with phagocytosis such as focal adhesion, the phagosome, and actin cytoskeleton regulation. Moreover, many genes involved in phagolysosomal function and antigen presentation were also upregulated after stimulation, indicating that mIgM+ B lymphocytes may degrade the internalized bacteria and present processed antigenic peptides to other immune cells. Interestingly, the type I interferon 3 (IFN I-3) gene was upregulated after L. lactis stimulation, and further analysis showed that the recombinant (r)IFN I-3 significantly enhanced phagocytosis of L. lactis and Edwardsiella tarda by mIgM+ B lymphocytes. In addition, significantly higher intracellular reactive oxygen species (ROS) levels were detected in mIgM+ B lymphocytes following rIFN I-3 treatment. We also found that IFN I-3 significantly upregulated Stat1 expression in mIgM+ B lymphocytes, and the enhancing effect of IFN I-3 on mIgM+ B lymphocyte-mediated phagocytosis was suppressed by fludarabine treatment. Collectively, these results demonstrate that mIgM+ B cell-mediated phagocytosis in the Japanese flounder is effectively triggered by bacterial infection, and further enhanced by IFN I-3, which itself may be regulated by Stat1.